Self-Assessment to Improve English Speaking Skills: an action research with Elementary School Ecuadorian students - Calero Vinueza, Nathaly Dayanara; Dos Santos, Jardel Coutinho; Galeas Arboleda, Gabriela; Cruz Quijije, Ana Maria (Arandu UTIC, 2024)
This study aimed to determine the impact of self-assessment on speaking skills among A2 movers’ students. The data analysis revealed that its use has a favorable effect on students' speech skills and showed that they could use the content in a real context. They incorporated reflection to be aware of their learning, understood their mistakes, and tried to improve their level of preparation for better results. At that time, they took responsibility for all the steps planned in innovation because they tested their effort and progress in each activity. In addition, the improvement demonstrated in the results of the evaluation carried out by the teacher with the rubric in the posttest was significant in the final part of the unit. The self-assessment helped students take the necessary corrective measures to be more prepared to do speech exercises. According to the students' perspectives, self-evaluation helped them improve their skills because they were able to identify areas of speech that needed to be improved and gradually, could reinforce their discourse to give better descriptions of places and people.